Does Work Time Flexibility Work? An Empirical Assessment of the Efficiency Effects for German Firms - Elke Wolf; Miriam Beblo (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
In this paper we assess the impact of flexible work time schedules on firm efficiency using representative establishment data for Germany. Following the approach by Battese and Coelli (1995), we estimate a stochastic production frontier and the determinants of technical efficiency simultaneously. The innovation of our study is that we draw on technical efficiency instead of productivity to appraise the success of flexible working hours. The results indicate that while the use of work time schedules with moderate flexibility is positively related to technical efficiency, highly flexible work time arrangements seem to be negatively correlated with an efficient organization of the work flow. However, these efficiency losses should not be interpreted as causal effects, because highly flexible work time schedules are most likely to be introduced in struggling firms.
Keywords: L23; D29; M54; 330; Stochastic production frontier; flexible work hours; efficiency; Arbeitszeitflexibilisierung; Unternehmensentwicklung; Technische Effizienz; Schätzung; Deutschland